2010
DOI: 10.1007/s11130-010-0159-3
|View full text |Cite
|
Sign up to set email alerts
|

Six Edible Wild Fruits as Potential Antioxidant Additives or Nutritional Supplements

Abstract: Total antioxidant activity of six non-cultivated but traditionally collected fruits from the south of Europe was assessed by measuring their ability to reduce the hydroxyl radical (OH) and hydrogen peroxide (H(2)O(2)), and their Trolox equivalent antioxidant capacity (TEAC). This antioxidant activity was compared with that shown by the synthetic antioxidants BHA (E-320), BHT (E-321) and propyl gallate (E-310). Total phenolics, ascorbic acid and the carotenoid content of the fruits were also analyzed. All fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
5
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 29 publications
(55 reference statements)
8
80
5
4
Order By: Relevance
“…The Crataegus monogyna fruits analyzed in our study showed values of (449.38 to 1438.52) mg gallic acid Eq·100 g -1 for FolinCiocalteu determination (table III), higher values than those reported by Ganhao et al [26] and Egea et al [29] [(450 and 216.61) mg gallic acid Eq·100 g -1 , respectively]. Applying the ABTS ·+ method, the values for fruits of C. monogyna ranged from (1.68 to 6.12) mmol Trolox Eq·100 g -1 of fresh fruit, which matches Ganhao et al, who provided 5.68 mM Trolox Eq·100 g -1 of fresh fruit [26], and are in accordance with the results of Froehlicher et al [30].…”
Section: Antioxidant Capacity Of the Fruitscontrasting
confidence: 56%
“…The Crataegus monogyna fruits analyzed in our study showed values of (449.38 to 1438.52) mg gallic acid Eq·100 g -1 for FolinCiocalteu determination (table III), higher values than those reported by Ganhao et al [26] and Egea et al [29] [(450 and 216.61) mg gallic acid Eq·100 g -1 , respectively]. Applying the ABTS ·+ method, the values for fruits of C. monogyna ranged from (1.68 to 6.12) mmol Trolox Eq·100 g -1 of fresh fruit, which matches Ganhao et al, who provided 5.68 mM Trolox Eq·100 g -1 of fresh fruit [26], and are in accordance with the results of Froehlicher et al [30].…”
Section: Antioxidant Capacity Of the Fruitscontrasting
confidence: 56%
“…Therefore, phenolic compounds are the major contributors of antioxidant potential. In accordance with our results, many authors observed the strongest correlation between the total phenolic content and antioxidant capacity methods (Egea et al, 2010;Erkan et al, 2011;Sahreen et al, 2010) Ferric reducing power activities were more associated with cupric reducing power activities than inhibition activity of linoleic acid oxidation. Good correlation was observed among total antioxidant capacity assays, namely phosphomolybdenum and β-carotene/linoleic acid assays (p<0.05).…”
Section: Principal Component Analysis (Pca) and Correlation Analysissupporting
confidence: 92%
“…Higher antioxidant activity has been attributed to higher total polyphenolic compounds present in fruit juice of Cap-Bon region. The difference of fruit juices in the DPPH scavenging activity could be explained by many factors, such as the ripening state of the fruits and environmental differences (Egea et al, 2010;Dou et al, 2013).…”
Section: Antioxidant Activities Of Extractsmentioning
confidence: 99%